1420 ViRtual prOficiency Based prOgression for Robotic Training (VROBOT): A Prospective Cohort Study Protocol. (12th October 2021) - Nathan, A; Patel, S; Georgi, M; Hang, K; Mullins, W; Asif, A; Fricker, M; Ng, A; Sridhar, A; Collins, J
Abstract: Introduction: Robotic surgery is an evolving field that requires specialist training. Historically, robotic surgery training has lacked standardisation. Recently, training centres have introduced proficiency-based modules and curriculums to certify and progress the skills of novice robotic surgeons. However, training tends to be self-directed and non-interactive. Limited interactive teaching does exist but can be inaccessible and expensive. We aim to validate the effectiveness of the current Fundamentals of Robotic Surgery (FRS) training curriculum with the addition of interactive virtual classroom teaching. Method: 16 novice surgical trainees will be assigned to two training groups. The interventions will be implemented following a one-week robotic skills induction. Both groups will receive access to the FRS curriculum for one week. The intervention group will additionally receive virtual classroom robotic skills training. The primary outcome will be the objective performance scores after training using a synthetic model based on task errors, time taken and contact pressure. In week 3, each group will receive the alternate intervention and objective performance scores will be measured to determine the trajectory of scores. Results: Significant objective performance improvement following the intervention will be indicative of intervention quality. Conclusions: This will be the first feasibility study evaluating the efficacy of interactive virtual robotic surgery training. It will determine the effect size of virtual classroom training on the development of basic robotic surgical skills in addition to the proficiency-based FRS curriculum. The findings will assist the development and implementation of further resource-efficient virtual robotic surgical skills training programs.